ANALISIS PENGARUH CUSTOMER REVIEW DAN INFLUENCER REVIEW TERHADAP PURCHASE INTENTION YANG DIMODERASI OLEH TRUST SERTA DAMPAKNYA KEPADA PURCHASE DECISION TOKO PRODUK FASHION DI SHOPEE - Vieri, Irham Athhar; Suyanto, AMA (JURNAL ILMIAH EDUNOMIKA, 2024)
This study analyzes customer reviews and influencer reviews on purchase intention and their impact on purchase decision at Shopee as a leading e-commerce platform in Southeast Asia. This study uses a quantitative approach with a sample of 385 respondents who have shopped for fashion products at Shopee, with data analysis using Partial Least Square Structural Equation Modeling (PLS-SEM). The results of the analysis show that customer reviews have a significant positive influence on purchase intention, as do influencer reviews. Trust moderates the relationship between customer reviews and purchase intention, but does not moderate the relationship between influencer reviews and purchase intention. Purchase intention has a significant positive influence on purchase decisions, while customer reviews have no significant influence on purchase decisions, and influencer reviews have a significant positive influence on purchase decisions. This illustrates the importance of customer and influencer reviews in influencing purchase intention and purchase decision, as well as the role of trust in amplifying the influence of customer reviews on purchase intention.